Hyperbolic Caching: Flexible Caching for Web Applications - Blankstein, Aaron; Sen, Siddhartha; Freedman, Michael J. (USENIX Annual Technical Conference (ATC), 2017)
Today’s web applications rely heavily on caching to reduce latency and backend load, using services like Redisor Memcached that employ inflexible caching algorithms. But the needs of each application vary, and significant performance gains can be achieved with a tailored strategy, e.g., incorporating cost of fetching, expiration time, and so forth. Existing strategies are fundamentally limited, however, because they rely on data structures to maintain a total ordering of the cached items.